From influencers to followers: unpacking credibility dimensions on food sharing intentions among Malaysian youth - Muhamad Shukur Suhaimi,; Siti Nor Amalina Ahmad Tajuddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Influencer marketing has blossomed into an increasingly prevalent method for products and brands to engage with followers, prompting interest in digital marketing and social media studies. However, due to a lack of source credibility, many social media influencers are experiencing a decline in content sharing from their followers despite investing time and money in developing engaging content. Yet, relatively little is known about influencers’ credibility in relation to food-sharing intentions among Malaysian youth. The present study addresses this gap by examining the relationship between social media influencers’ credibility and followers’ sharing intention on food content. By adopting a quantitative approach with a correlational design, this study aimed to discover the relationship between social media influencers’ perceived expertise, trustworthiness and attractiveness with followers’ sharing intention towards the food content among Malaysian youths. The researcher employed a probability sampling technique using a random selection of respondents for the sampling. The findings showed that the level of perceived source credibility dimensions and followers’ sharing intention towards the food content among Malaysian youths was mostly moderate. Pearson correlation analysis revealed a significant relationship between social media influencers’ source credibility dimensions and followers’ sharing intention towards the food content among Malaysian youths. The study leverages a deeper understanding of social media influencers through the dimension of credibility and food-sharing intention and thus contributes to developing a more successful social media strategy to engage with netizens.